2002
DOI: 10.1007/s00467-002-0853-y
|View full text |Cite
|
Sign up to set email alerts
|

Ethics of paid organ donation

Abstract: As the waiting list of patients requiring organ transplantation grows, there is a subtle but noticeable shift in society towards accepting organs as a commodity which can be paid for. Although nowhere is the organ trade legal, the commerce of organs goes on in different parts of the world, especially in developing countries such as India. This is largely due to societal and governmental failure to implement the existing "transplant laws". It is high time the medical profession ceased being an accomplice to thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 11 publications
0
21
0
2
Order By: Relevance
“…In a study done on the responses of relatives of post-mortem cases, it was revealed that out of the potential post-mortem donors, only 44.3% of relatives of such cases gave consent for donation after intensive counseling. (17) Mass media in the form of television, newspapers, magazines, and posters were important sources of information on eye donation. Other studies also found publicity campaigns and the media to be the major sources of information on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…In a study done on the responses of relatives of post-mortem cases, it was revealed that out of the potential post-mortem donors, only 44.3% of relatives of such cases gave consent for donation after intensive counseling. (17) Mass media in the form of television, newspapers, magazines, and posters were important sources of information on eye donation. Other studies also found publicity campaigns and the media to be the major sources of information on this issue.…”
Section: Discussionmentioning
confidence: 99%
“…I am afraid that the incentives suggested in the very recent paper by Delmonico et al [14] would not suffice in the United States, although their thoughtful approach should be applauded. In my view this paper certainly does not present a worldwide solution, particularly in the face of the totally negative approach to the "sale" of an organ of such workers as Phadke and Anandh [5]. The RTx problem will only increase in size and importance with the ever-growing lists of patients awaiting RTx, worldwide.…”
mentioning
confidence: 87%
“…Accepting the possibilities and biological benefits of living non-related organ donation has resulted in an emerging debate about the advantages of paid living kidney donation [5][6][7][8][9][10][11][12][13][14][15][16][17]. The major arguments in favor of paid living kidney donations include the opportunity of reducing the shortfall in donor organs, short waiting times for renal transplantation and economic benefits for the donor and his or her family.…”
Section: Paid Living Organ Donationmentioning
confidence: 99%